2011
DOI: 10.1002/chem.201102293
|View full text |Cite
|
Sign up to set email alerts
|

Water‐Soluble Prodrug of Antimicrotubule Agent Plinabulin: Effective Strategy with Click Chemistry

Abstract: Experimental results for methane and carbon dioxide diffusion in coal, as reported in the literature, often lead to diffusion rates of CO2 appearing to be much greater than that of CH4. The interpretation sometimes offered that the diffusion coefficient for CO2 is 1–2 orders of magnitude higher than that of CH4, violates fundamental principles. Nevertheless, the experimental observations require explanation. In this article, we: (a) Develop simplified models for the fast estimation of transport coefficients. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 74 publications
(61 reference statements)
0
18
0
Order By: Relevance
“…56 exhibited an IC 50 value that was one-tenth the value of 7 under normal conditions. 62,63) The reduced IC 50 value was attributed to the direct reaction of the monolactim prodrug 56 with small amounts of esterases produced by the cells or with the inner components of the cells.…”
Section: Evaluation Of Cytotoxicitymentioning
confidence: 89%
See 1 more Smart Citation
“…56 exhibited an IC 50 value that was one-tenth the value of 7 under normal conditions. 62,63) The reduced IC 50 value was attributed to the direct reaction of the monolactim prodrug 56 with small amounts of esterases produced by the cells or with the inner components of the cells.…”
Section: Evaluation Of Cytotoxicitymentioning
confidence: 89%
“…Therefore, we attempted to develop a water-soluble prodrug of 7 to avoid the safety or quality of life risks to patients. 50,51) …”
Section: Development Of a Water-soluble Prodrug Of Plinabulinmentioning
confidence: 99%
“…23,24 Prodrug 2 exhibits a sufficiently high water solubility (6.4 mg/mL) and can be used as an intravenous agent. Ester cleavage of prodrug 2 by esterase yields the parent compound 1 23 .…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the water-solubilizing triazole auxiliary, which was cleaved from the mother skeleton via an esterase hydrolysis reaction, was shown to be cellularly non-toxic. 11) These results suggested that it was worthwhile to pursue further optimization of this prodrug system.…”
mentioning
confidence: 99%
“…4) Therefore, a variety of water-soluble paclitaxel prodrugs have been developed to improve the patient's burden. [5][6][7][8][9] Previously, we reported the design and synthesis of a water-soluble prodrug of plinabulin (1) 10) as a monolactim serine-type derivative 2 11) using click chemistry [12][13][14] (Fig. 1).…”
mentioning
confidence: 99%